Adsorption of NO2, NH3 on monolayer MoS2 doped with Al, Si, and P: A first-principles study - Luo, Hao; Cao, Yijiang; Zhou, Jing; Feng, Jumeng; Cao, Jiamu; Guo, Hai (Chemical physics letters, 2016)
•Density of states and charge of transfer are connected to discuss how doped MoS2 improves gas adsorption properties.•Multiple NO2 molecules adsorption on Si-doped MoS2.•Si-doped MoS2 is indicated to be the most suitable sensing material of all three systems. Using first-principles calculations, we investigate the adsorption of NO2, NH3 gas molecules on Al-, Si-, and P-doped monolayer MoS2. The structural properties, electronic properties, and magnetic properties are obtained. The successful experimental preparation of nitrogen-doping MoS2 indicates the structural stability of Si-, P-doped monolayer MoS2. Compared with the adsorption of NO2 and NH3 on pristine monolayer MoS2, Al-, Si-, and P-doped monolayer MoS2 improve the structural stability of that of NO2 and NH3. On the other hand, the dopant atoms increase the effects of orbital hybridization between NO2, NH3 molecules and monolayer MoS2, and promote the transfer of electrons.